Modeling Study of Interaction between Fluid Flow and Pipe Wall Formed in Piping Erosion Phenomenon with SPH Method - Suntarto, Rut Puspaningtyas; Sjah, Jessica; Rika, R.R. Dwinanti; Bahsan, Erly (Universitas Ibn Khaldun Bogor, 2024)
This study observes the interaction between fluid flow and the solid particles using Smoothed Particle Hydrodynamics (SPH) as a numerical approach with DualSPHysics platform and the flow assumed as a laminar flow with Re of 25, 50, and 100. As an approach study of internal piping erosion phenomenon, there are two types of pipes simulated, pipe with smooth wall and rough wall with different geometry and height of roughness. The geometry of roughness simulated are semi – circular ribs, triangular ribs, and rectangular ribs. The evaluated output of this research is the friction coefficient and velocity distribution occurring. In the case of flow through smooth wall, it is found that the increase of Reynolds number causes the decrease of friction coefficient. The next case of flow through rough walls shows that the height and shape of roughness affect the friction coefficient and velocity contour of the flow.